(3efgGL GdOcGf hOSJhQ GdCYjGf aj JQcjH GdCOhjI GdfGaYI ddEfSGfs - (3Gdchgjf GdYWGQ GdGSQGFjdj , OGhO Hf CHj fUQ Hf MaGX, CHh Gdefj,J (B608 (3g` s ((3YHO Gddg Hf eQGO s)
(3ChdgG (B:s
(3eG Jhajbi EdG HGddg Ydjg JhcdJ gPG efgGL GdOcGf hOSJhQ GdCYjGf eeG jfHZi Cf jMJhi Ydjg GdMeO ddg GdPi djS HPi HOGjI s
(3BNQgG (B:s
(3jOb GdLejY hjfNd jDNP RjJ ef cd hGMO ChbjJjf hjWHN HgeG GdCOhjI hjSJYed eSGAkG hUHGMkG s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B143s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1871s
Keywords: (3GdWHs